2019
DOI: 10.1093/aobpla/plz015
|View full text |Cite
|
Sign up to set email alerts
|

Patterns ofmtDNA variation reveal complex evolutionary history of relict and endangered peat bog pine (Pinus uliginosa)

Abstract: Estimates of genetic differentiation at intra- and interspecific level are often hindered by the lack of suitable molecular markers. Low phylogeographic resolution limits development of appropriate conservation strategies especially in case of endangered forest tree species with small and disjunct distribution. In this study, we assessed fine-scale genetic structure of relict and endangered peat bog pine ( Pinus uliginosa ) and two other closely related European pine species ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…Although the number of samples from individual populations was limited, the analysis showed the array's potential for discriminating populations at broad spatial scales. Within species, populations showed clear structure, while those from P. uliginosa appeared to be most clearly diverged, supporting results from a recent study using mt DNA markers (maternally inherited in pines; Łabiszak, Zaborowska, & Wachowiak, 2019). There was evidence for distinct population clusters in other species for highly diverged populations at the species' margins (including P. sylvestris in Scotland, P. mugo from the Abruzzi Mountains in Italy and P. uncinata from Castiello de Jaca in Spain).…”
Section: Discussionsupporting
confidence: 80%
“…Although the number of samples from individual populations was limited, the analysis showed the array's potential for discriminating populations at broad spatial scales. Within species, populations showed clear structure, while those from P. uliginosa appeared to be most clearly diverged, supporting results from a recent study using mt DNA markers (maternally inherited in pines; Łabiszak, Zaborowska, & Wachowiak, 2019). There was evidence for distinct population clusters in other species for highly diverged populations at the species' margins (including P. sylvestris in Scotland, P. mugo from the Abruzzi Mountains in Italy and P. uncinata from Castiello de Jaca in Spain).…”
Section: Discussionsupporting
confidence: 80%
“…Those results may reflect their rapid divergence after the split, facilitated by the geographic isolation and contemporary disjoint distribution of sympatric populations found only in the Alps, with P. uncinata primarily located in the western and P. mugo in the eastern parts of the mountains. Patterns of mitochondrial DNA variation support this ongoing divergence, as both species, could be clearly delineated by mitochondrial markers, and P. uncinata harbors unique and fixed mitotypes [33]. Nevertheless, there is evidence for interspecific gene exchange between those pines in their contact zone in the Alps [82].…”
Section: Interspecific Gene Flowmentioning
confidence: 73%
“…The wide distribution of P. sylvestris and its known long-distance migration associated with postglacial recolonization of Europe could facilitate overlap with other pine species and locally restricted gene flow. Previous studies reported similarities between Scots pine populations from Poland and Finland [85,86], reflecting their common phylogeographic history, and mitotype sharing between P. uliginosa, P. mugo, and P. sylvestris in their contact zones was also reported [33,80].…”
Section: Interspecific Gene Flowmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies on P. uliginosa were mostly focused on its complex evolutionary history and on the taxonomic relationships with its close relatives: Pinus sylvestris and pines from a broader group called Pinus mugo complex, including dwarf mountain pine ( P. mugo Turra) and Pyrenean pine ( Pinus uncinata Ramond) (Hamernik & Musil, 2007; Boratyńska & Lewandowska, 2009; Wachowiak & Prus‐Glowacki, 2009; Łabiszak et al, 2019). These species diverged from their common ancestors about 5 million years ago (Wachowiak et al, 2011).…”
Section: Introductionmentioning
confidence: 99%